The effect of principal transformational leadership on teacher innovative behavior: the moderator role of uncertainty avoidance and the mediated role of the sense of meaning at work - Bao, Yuangen (Frontiers in Education, 2024)
Given the rapid technological advancements and increasing global uncertainties, principals' promoting teacher innovative behavior (TIB) is fundamental for schools to enhance effectiveness and achieve sustainable competitive growth. However, previous research on the impact of principal transformational leadership (PTL) on TIB has yielded conflicting results. Drawing upon social cognitive theory and leadership substitution theory, this study constructs a model to elucidate the mediating role of teachers' sense of meaning in work (TMW) between PTL and TIB, as well as the moderating role of teachers' uncertain avoidance (TUA) in mainland China. By employing the PROCESS plug-in in SPSS to analyze data from 295 questionnaires, our findings demonstrate that PTL positively influences TIB, with TMW serving as a mediator in this relationship. Furthermore, TUA moderates both direct and indirect relationships mentioned above. These findings shed light on the underlying mechanisms through which principal transformational leadership impacts teacher innovative behavior. The implications derived from this conclusion offer valuable managerial insights for principals seeking to promote TIBs.